Research on Theory and Practice of Comprehensive Performance Evaluation of Financial Operation in Minority Concentrated Regions in the New Era (JOURNAL OF ADVANCES IN LINGUISTICS, 2024)
In order to meet the needs of China’s high-quality development, the minority concentrated regions must allocate public resources efficiently. It is urgent to promote the effective implementation of financial budget performance management in minority concentrated regions. Through the investigation, we summarized the progress and effectiveness of the financial budget performance management in different countries and deeply analyzed the main problems faced by the financial budget performance management in the minority concentrated regions. These problems include the insufficient innovation of the budget performance management system in promoting the county financial effort in each province and below, the further strengthening of the scientificity of the budget performance management evaluation indicator system to promote the county financial autonomy, and the urgent need to improve the financial budget performance management ability at the county level. After the systematic sorting out of the related documents on comprehensive performance evaluation of financial operation, the author constructed an analysis framework of the comprehensive performance evaluation of the financial operation in the minority concentrated regions, which includes two dimensions, “financial operation behavior” and “government budget function”. Under this framework, we not only clearly elaborated the basic composition of the comprehensive performance evaluation of financial operation, but also determined its core evaluation indicators. In addition, the system also deeply analyzed the effectiveness and deficiency of the county financial operation and provided valuable reference for the local government to make decisions, and also provided valuable experience for other county and even wider local financial management.